2019
DOI: 10.4085/1062-6050-387-17
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Newly Credentialed Athletic Trainers During Their Transition to Practice

Abstract: Context Understanding the challenges faced by newly credentialed athletic trainers (ATs) as they transition into clinical practice could assist employers and professional programs in developing initiatives to enhance this transition. Objective To explore the challenges faced by newly credentialed ATs during their transition from student to autonomous practitioner. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Many new ATs cited role ambiguity as a source of stress during the transition. 21 This role ambiguity is related to uncertainty about certain policies, procedures, administrative duties, and their role. One way to help new ATs understand their role is through thorough orientation and continued onboarding.…”
Section: Comfort Levelmentioning
confidence: 99%
See 4 more Smart Citations
“…Many new ATs cited role ambiguity as a source of stress during the transition. 21 This role ambiguity is related to uncertainty about certain policies, procedures, administrative duties, and their role. One way to help new ATs understand their role is through thorough orientation and continued onboarding.…”
Section: Comfort Levelmentioning
confidence: 99%
“…11 Although participants in our study had been employed for only approximately 2 to 3 months, which was not long enough to adequately determine success or failure, individuals who perceived higher levels of mentorship and support were less likely to consider leaving the profession. Prior researchers 21 demonstrated the benefits of mentorship in the transition to practice, despite mentor inaccessibility being cited as a challenge during this time. Our results indicated that most new ATs felt they could go to their mentor or supervisor anytime they had a question.…”
Section: Mentorship and Supportmentioning
confidence: 99%
See 3 more Smart Citations